More Than 200 Years Later: Gluvia brunnea sp. nov. (Solifugae, Daesiidae), a Second Species of Camel Spider from the Iberian Peninsula - Cristian Pertegal; Pablo Barranco; Eva De Mas; Jordi Moya-Laraño (Insects, 2024)
We present the description of a new species of Solifugae from the Iberian Peninsula, Gluvia brunnea sp. nov., which has been found so far in southeast Spain. The morphological description is accompanied by molecular and multiple factor analyses, jointly giving full support to the specific status of the taxon. Finally, we discuss the intraspecific variability of both species, G. dorsalis and G. brunnea sp. nov., and the recent history of the genus. We also discuss the usefulness of multiple factor analysis for quantitatively separating species, and we stress that some specimens of this new species were found in Mesovoid Shallow Substratum stations, representing the very first time that Solifugae have been captured in this type of trap.